Exploring gender perceptions of resource ownership and their implications for food security among rural livestock owners in Tanzania, Ethiopia, and Nicaragua - Galiè, Alessandra; Mulema, Annet A.; Mora Benard, María Alejandra; Onzere, S.; Colverson, Kathleen E. (Springer, 2015)
Productive resources are essential to the livelihoods and food security of the world's rural poor. Gender-equal ownership of resources is considered key to increasing agricultural productivity, equity, and food security. However, there has not been much research about local understandings of ownership particularly in the Global South. In addition, research is also lacking about how concepts of ownership affect food security at the household level. This paper discusses the variability of local understanding of ownership by showing seven domains resource ownership was associated with by a small cohort of respondents. It shows the flexibility of systems governing resource entitlements among the studied communities and their impact on food security. It shows that, irrespective of these understandings and systems, resource arrangements favored men. The authors argue that an understanding of local meanings of ownership might reveal important and unnoticed aspects of resource allocation, as well as provide guidance for initiatives that seek to provide locally relevant approaches to improving gender equity.